DEKOMPOSISI SERASAH DAUN Rhizophora apiculata DAN KONTRIBUSI TERHADAP UNSUR HARA DI PERAIRAN PULAU SEMBILAN KECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT - M. Ridho Santoso; Yunasfi Djayus; Ahmad Mutadi (AQUACOASTMARINE, 2016)
The mangrove litter which has been decomposed contributes organic matter as source of nutrients, mangrove and natural food source for many species of fish and other organisms in the mangrove ecosystem. The purpose of this research is to know the decomposition of R. apiculata leaf litter and to know the nutrient content of carbon (C), nitrogen (N) and phosphorus (P) in the R. apiculata leaf litter which been released during the decomposition time. This research was done at the waters of the Pulau Sembilan Districs Langkat District Pangkalan Susu, North Sumatra Province during March until June 2016. This research used purposive sampling method at three stations and the determination of the station is done by seeing the availability of R. apiculata at the waters of the Pulau Sembilan. The results showed that the decomposition of R. apiculata litter leaf on day 75 are 8,53 in stasiun I, 8,58 in station II and 10,18 in III station. The fastest decomposition is the station I with 10,18 and the slowest decomposition is the station I with 8,53. The nutrient of carbon during decomposition in 75 days are 17,41% at station I, 15,84% at station II and 17,41 % at station III. Nutrient of nitrogen which beendecomposed on day 75 are 0,98% in station I, 1,18 % in station II and 1,18 % in station III. Nutrient of phosphorus during decomposition in 75 days are 0,08% in station I, 0,09 % in station II and 0,10 % in station III.Keywords : Decomposition, Pulau Sembilan, R. apiculata. nutrient.